SEBUTAN DAN SAPAAN DALAM ISTILAH KEKERABATAN BAHASA TONTEMBOAN SUATU KAJ IAN LINGUISTIK ANTROPOLOGI - Stelnie H. Perutu (Kadera Bahasa, 2011)
The research about naming and addressing in Tontemboan Language Kinship Terminology is necessary and still relevant nowadays due to a lot of supporting factors for the language resistance such as attitude and appreciation which are about to be forgotten by the Minahasans. In fact, the director of Kawan Pustaka ( 2004.130) said that “the culture identity.... is respected along with the changing of the time and civilization". The cultural identity includes the language. The method which is used, in this research is a qualitative method. This research is located in Motoling Timur district, Motoling Barat district, and Kumelembuai district, the southeast of Minahasa. The results of this research are some blood relationship kinship terminologies such as inang, amang, bu, susi, mom, none, tete, nene kundu, lete kundu, apo, toyaang luluna, toyaang karuwa, toyaang, uner, toyaang wobas, pakakaan, tuwari, and some in laws terminologies such as penanaan, ambalesa, kalo, kawuleng, kasule, kalaley, kasungku. The conclusion of this research is that the native speakers of Tontemboan language know the blood-relationship kinship terminology, the in-law's terminology, and the additional kinship terminology. The collected data ﬁmctions as naming, addressing and naming as well as addressing. Furthermore, those terminologies contain the cultural meaning.